Separation Without Exclusion in Financial Insurance. Issue 4 (10th March 2014) - Stephens, Eric; Thompson, James R.
Abstract: This article develops a model of linearly priced financial insurance sold by default‐prone insurers. It shows that when insurers differ in their default probabilities there can exist equilibria in which different risk types partially or completely self‐sort into insurance contracts offered by different insurers. Partial separation can occur when insurer default and insurance risks are uncorrelated. Full separation is possible when they are correlated. For example, low‐risk insured parties may match with higher default‐risk insurers, while high‐risk insured parties match with lower default‐risk insurers.